Impaired Fear Extinction Due to a Deficit in Ca2+ Influx Through L-Type Voltage-Gated Ca2+ Channels in Mice Deficient for Tenascin-C - Morellini, Fabio; Malyshev, Aleksey; Volgushev, Maxim; Chistiakova, Marina; Papashvili, Giorgi; Fellini, Laetitia; Kleene, Ralf; Schachner, Melitta; Dityatev, Alexander (Frontiers in Integrative Neuroscience, 2017)
Mice deficient in the extracellular matrix glycoprotein tenascin-C (TNC-/-) express a deficit in specific forms of hippocampal synaptic plasticity, which involve the L-type voltage-gated Ca2+ channels (L-VGCCs). The mechanisms underlying this deficit and its functional implications for learning and memory have not been investigated. In line with previous findings, we report on impairment in theta-burst stimulation-induced long-term potentiation in TNC-/- mice in the CA1 hippocampal region and its rescue by the L-VGCC activator Bay K-8644. We further found that the overall pattern of L-VGCC expression in the hippocampus in TNC-/- mice was normal, but Western blot analysis results uncovered upregulated expression of the Cav1.2 and Cav1.3 α-subunits of L-VGCCs. However, these L-VGCCs were not fully functional in TNC-/- mice, as demonstrated by Ca2+ imaging, which revealed a reduction of nifedipine-sensitive Ca2+ transients in CA1 pyramidal neurons. TNC-/- mice showed normal learning and memory in the contextual fear conditioning paradigm but impaired extinction of conditioned fear responses. Systemic injection of the L-VGCC blockers nifedipine and diltiazem into wild-type mice mimicked the impairment of fear extinction observed in TNC-/- mice. The deficiency in TNC-/- mice substantially occluded the effects of these drugs. Our results suggest that TNC-mediated modulation of L-VGCC activity is essential for fear extinction.